Sustainable tourism souvenirs: fostering cultural heritage preservation through local handicraft product - Wang, Yanyan; Alli, Hassan; Md Ishak, Siti Mastura (Global Academic Excellence, 2023)
The study aims to investigate the relationship between cultural tourism and traditional handicraft experiences on local handicrafts products namely souvenirs. It explores the significance of souvenir products through sustainable tourism practices and preserving cultural heritage. A qualitative approach is used to analyse the tourism souvenir in the market and proposes a new recommendation to meet the demands. Literature review, interviews, and case studies are employed to explore a strategy for enhancing the commercial value of tourism souvenirs. Interviews with master craftsmen, practitioners, and consumers provided insights the resource development, product innovation, production organisation, and market positioning. It also obtained a good understanding of customer experiences related to local handicraft products for effective marketing strategies based on customer experiences. The finding indicates that the sustainability of tourism souvenirs plays a crucial role in cultural heritage preservation, supporting the local economy, and enhancing overall tourism experiences for tourists as well as promoting traditional handicrafts, safeguarding indigenous knowledge, and facilitating cultural exchange between tourists and local artisans.